The Forms of Michael Field - Richardson, LeeAnne M. author. aut Link
XI, 282 p. 5 illus.
Keywords: Michael Field, the poetic identity created by Katharine Bradley (1846-1914) and her niece Edith Cooper (1862-1913), ceaselessly experimented with forms of identity and forms of literary expression. The Forms of Michael Field argues that their modes of self-creation are analogous to their poetic creations, and that exploring them in tandem is the best way to understand Michael Field’s cultural and literary importance. Michael Field deploys a different form in each volume of their lyric poetry: translations of Sappho, ekphrasis, songs, sonnets, and devotional verse. They also appropriate and revise the dramatic genres of verse tragedy and the masque. Each of these experiments in form enable Michael Field to differently address the cultural questions that beset late-Victorian women writers. Drawing on the insights of new lyric studies and new formalism, this book analyzes Michael Field’s continual quest for the aesthetic forms that best express their evolving ideas about identity and sexuality, gender and sacrifice, lyric voice and authority. LeeAnne M. Richardson is Associate Professor of English at Georgia State University in Atlanta, Georgia, USA.